A computational fluid dynamic study of the filling of a gaseous hydrogen tank under two contrasted scenarios. (30th June 2022) - Gonin, Rémi; Horgue, Pierre; Guibert, Romain; Fabre, David; Bourguet, Rémi; Ammouri, Fouad; Vyazmina, Elena
Abstract: The filling of a horizontal hydrogen tank designed for light duty vehicles is investigated by means of multi-physics numerical simulations. The simulation approach, implemented in OpenFOAM, includes compressible Reynolds-Averaged Navier-Stokes (RANS) modeling of the fluid flow and heat transfer in the solid parts. The simulations are carried out for 2D-axisymmetric and 3D configurations. Two filling scenarios of the tank, leading to two distinct thermal behaviors, i.e. homogeneous versus heterogeneous, are simulated and compared to the experimental data issued from the HyTransfer project. In the homogeneous case, where no thermal stratification occurs, the 2D and 3D simulation results are close to the experimental ones. A phenomenon of jet flapping is identified via the 3D simulation. In the heterogeneous case, where thermal stratification occurs, the 3D simulation captures an averaged temperature close to the experimental one, as well as the instant at which the thermal gradients appear. It also captures the deflection of the jet, which is a central element in the emergence of the thermal gradients. Highlights: 2D axisymmetric and 3D simulations are carried out using free software OpenFOAM. Jet deflection and flapping, and onset of stratification are captured. The k  −  ω SST turbulence model underestimates the thermal gradients.